Mapping the Future of Particle Radiobiology in Europe: The INSPIRE Project - Henthorn, Nicholas T.; Sokol, Olga; Durante, Marco; De Marzi, Ludovic; Pouzoulet, Frederic; Miszczyk, Justyna; Olko, Pawel; Brandenburg, Sytze; van Goethem, Marc Jan; Barazzuol, Lara; Tambas, Makbule; Langendijk, Johannes A.; et al. (Frontiers in Physics, 2020)
Particle therapy is a growing cancer treatment modality worldwide. However, there still remains a number of unanswered questions considering differences in the biological response between particles and photons. These questions, and probing of biological mechanisms in general, necessitate experimental investigation. The “Infrastructure in Proton International Research” (INSPIRE) project was created to provide an infrastructure for European research, unify research efforts on the topic of proton and ion therapy across Europe, and to facilitate the sharing of information and resources. This work highlights the radiobiological capabilities of the INSPIRE partners, providing details of physics (available particle types and energies), biology (sample preparation and post-irradiation analysis), and researcher access (the process of applying for beam time). The collection of information reported here is designed to provide researchers both in Europe and worldwide with the tools required to select the optimal center for their research needs. We also highlight areas of redundancy in capabilities and suggest areas for future investment.